2020
DOI: 10.1016/j.ccell.2020.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Cyto-Immuno-Therapy for Cancer: A Pathway Elicited by Tumor-Targeted, Cytotoxic Drug-Packaged Bacterially Derived Nanocells

Abstract: Highlights d EnGeneIC Dream Vector (EDV) nanocells induce an antitumor innate immune cell response d EDV treatment results in tumor-specific T cells and an adaptive immune response d EDV treatment elicits a predominantly Th1 response d Dual assault on EDV-treated tumors confers long-term survival

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 41 publications
0
40
0
Order By: Relevance
“…The DURAclone technology used here has been successfully applied for the detection of regulatory T cells (Tregs), naïve/memory T cells and other immune cells in the peripheral blood of healthy human donors in previous work (33)(34)(35). Furthermore, the feasibility of this technology for immunomonitoring of cancer patients has been proven by the detection of minimal residual disease (MRD) in myeloma patients and by analyzing blood cells of cancer patients in response to immunotherapeutic nanoparticles (36,37). In addition, the introduced technology is not limited to CD19-targeting CAR approaches and can be readily adapted to the evaluation of other CAR immunotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…The DURAclone technology used here has been successfully applied for the detection of regulatory T cells (Tregs), naïve/memory T cells and other immune cells in the peripheral blood of healthy human donors in previous work (33)(34)(35). Furthermore, the feasibility of this technology for immunomonitoring of cancer patients has been proven by the detection of minimal residual disease (MRD) in myeloma patients and by analyzing blood cells of cancer patients in response to immunotherapeutic nanoparticles (36,37). In addition, the introduced technology is not limited to CD19-targeting CAR approaches and can be readily adapted to the evaluation of other CAR immunotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been demonstrated that minicells (chassis of mini-SimCells) can be loaded to release super-cytotoxic anti-tumor drug. 51 …”
Section: Discussionmentioning
confidence: 99%
“…Another way to circumvent tumor resistance is to use highly cytotoxic compoundssuch as the PNU-159682 metabolite [161] that cannot be injected systemically because of their high toxicity. Systemic vectorization of this drug in EGFR-targeted bacterial minicells showed significant tumor reduction and immune activation with no side effects in immunocompetent breast and colorectal murine models but also lung and colorectal human cancer xenografts [162].…”
Section: Fighting Resistancementioning
confidence: 98%